Early flowering, genetic dissimilarity and clustering of lettuce cultivars with thermoinhibition tolerant seeds - Catao, Hugo Cesar R. M.; Gomes, Luiz Antonio Augusto; Azevedo, Alcinei M.; Siquieroli, Ana Carolina S.; Maciel, Gabriel M.; Freitas, Pamela G. N. [UNESP] (Assoc Brasileira Horticultura, 2022)
High temperatures interfere with lettuce cropping. Thermoinhibition of seed germination and early flowering cause important losses for farmers. The objectives of this work were to evaluate the tolerance to early flowering, to verify the genetic dissimilarity and to select lettuce cultivars tolerant to seed thermoinhibition. 18 cultivars were evaluated. The number of days until the first anthesis was verified for early flowering. Regarding seed thermoinhibition, the first and final germination counting and germination speed index were evaluated, using temperatures of 20, 25, 30 and 35??C. The analyses were performed immediately after harvest and after six months under storage. The genetic dissimilarity was obtained using the Tocher Graph optimization and hierarchical UPGMA methods. Regression models were adjusted, and curves??? clustering was performed by testing the identity of the models. Early flowering was observed in cultivars Floresta, Colorado, Grand Rapids, and Everglades. Cultivars showed genetic variability and are dissimilar regarding tolerance to thermoinhibition. By clustering the regression equations, it was possible to select thermoinhibition tolerant cultivars.
Keywords: Lactuca sativa; Anthesis; Genetic variability; Multivariate statistics; Temperature